The Role of Family Support in Stress and Anxiety Conditions in The Elderly with Chronic Kidney Disease Underwent Hemodialysis Therapy - Pratiwi, Wahyu Nur; Gayatri, Paramita Ratna; Astutik, Wahyu Sri; Pratama, Yuan Guruh; Ayyaroh, Faridlatul A. (STIKES Adi Husada, 2023)
People with chronic kidney disease who underwent hemodialysis therapy programs are at great risk of experiencing cognitive impairment, as well as mental health disorders such as emotional disturbances, anxiety, and stress, so they need support from their families. Psychosocial problems are very prone to be experienced by people with chronic disease, especially the elderly, however, nurses tend to raise physical nursing problems, which makes psychosocial problems are still not sufficiently addressed as the implication. This study aims to determine the effect of family support on stress and anxiety levels in the elderly with chronic kidney disease undergoing hemodialysis therapy. Respondents in this study were elderly people with kidney disease who underwent hemodialysis therapy at Bhayangkara Hospital, Kediri City with certain criteria. The number of respondents who participated was obtained by accidental sampling technique. The data was obtained using a questionnaire for each variable and then it was tested using the Spearman correlation test. The results obtained show a significant value for both family support with stress levels and anxiety levels. This proves that family support has a good relationship with stress levels and anxiety levels.